BACTERIOLOGICAL EVALUATION AND ANTIBIOTIC SUSCEPTIBILITY PROFILE OF ISOLATES FROM READY- TO- EAT FRIED FISH. - Baba, John; I. L. Muhammad,; S. Danfulani,; S. M. Adamu,; A. T. Olutimayin,; A. Daniel, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
The study was carried out to ascertain the level of bacterial contamination of ready-to-eat fried fish hawked in Lapai metropolis of Niger state, Nigeria. Fried fish samples were collected from two different markets in Lapai. The bacterial load of the samples was determined using the pour plate technique. Bacteria growth was sub-cultured on MacConkey agar and Mannitol salt agar. Identification and characterization of various isolates were based on Gram staining technique and conventional biochemical tests. Results indicated that the mean bacteria population across the two markets after sampling for two (2) months ranged from 7.0 x 104 to 8.4 x 106 cfu/mg. The lowest bacteria population of 7.0 x104 cfu/mg occurred in the samples from the main market, while the highest bacteria population of 8.4 x 106 cfu/mg occurred in the samples from Badeggi market. Pseudomonas aeruginosa isolates had the highest distribution of 4 (44.5%), while Streptococcus spp isolate had the least distribution of 1 (11.1%). Bacillus subtillis and Staphylococcus aureus isolates had equal distribution of 2 (22.2%). Antibiotic susceptibility test was conducted on the isolates, and the result showed that S. aureus was 100% resistant to all the antibiotics used in the research study. Bacillus subtilis showed resistance to all the antibiotics, except Levofloxacin and Rifampicin to which the isolates were susceptible by 50%. Streptococcus spp was 100% resistant to Ampiclox, Erythromycin, Chloramphenicol, Norfloxacin, Amoxil and Rifampicin, but showed 100% susceptibility to Gentamicin, Levofloxacin, Ciproflox and Streptomycin. The isolates of P.aeruginosa were moderately susceptible to all the antibiotics used, but resisted Ampiclox and Norfloxacin. The findings of this research indicated that ready- to- eat foods are potential vehicles for transmitting food borne illnesses, therefore, there is the need to develop practical strategies that would prevent microbial contamination of street hawked foods.